PEMANFAATAN KAWASAN-KAWASAN TEKNOLOGI PENDIDIKAN DALAM MENINGKATKAN HASIL BELAJAR - Herawati Daulae, Tatta (IAIN Padangsidimpuan, 2019)
Good learning outcomes are the ideals and expectations of every student and collage student, education provider, government and community. Educational institutions are one place to achieve learning outcomes, preparing students to have knowledge, attitudes, and skills. Then the education provider must be able to carry out various policies and renewal efforts in the field of education. Teachers and lecturers as managers of learning are responsible for organizing and implementing learning well in order to achieve good learning outcomes. So one of the supporting factors in achieving good learning outcomes is to utilize educational technology areas in learning activities